Three Generations of Family Culinary Business: Study Grounded Theory in Jakarta - Fajar Andika Prabowo; Usep Suhud; Ari Warroka (Profesional Muda Cendekia Publishing, 2022)
This study aims to identify the efforts of legendary culinary entrepreneurs in Jakarta to maintain for decades. The research was conducted using a qualitative approach. Researchers use an approach that is based on grounded theory. Research resource persons were taken based on purposive sampling method. The collection technique used by the researcher is observation, in-depth interviews, and documentation. Analysis of the data used is Nvivo12. Based on the results of qualitative research using a grounded theory approach, regarding the efforts of legendary culinary entrepreneurs in Jakarta to maintain family culinary businesses for decades, several conclusions can be drawn regarding the efforts of the next generation of entrepreneurs, including (1) Innovating culinary products and marketing innovations by collaborating with online applications, Gofood, Tokopedia, and Facebook. One of the marketing strategies used in an effort to maintain a culinary business is using social media. (2) One of the efforts to maintain a family culinary business is to maintain quality. This effort can maintain family businesses, especially those that do not change the taste of the previous generation and continue to provide good service to consumers. (3) Further efforts to encourage legendary culinary businesses to last for decades because of the trust from their parents. This effort is not only a desire for business profits but also a pride from the next generation in introducing to millennials that many legendary culinary delights are still surviving in running their business for decades.